Fomulasi Minuman Fungsional Berbasis Kacang Gude dan Tempe - chaerunnimah chaerunnimah; Retno Sri Lestari; Hijrah Asikin (Media Gizi Pangan, 2022)
Pigeon pea and tempeh are local foods that are rich in nutrients. This functional drink is a development of the previously made peanut drink formulation. This functional drink of gude and tempeh beans with the addition of arabic gum as a stabilizer. Analyzing the effect of adding gum arabic through organoleptic tests and knowing the food safety of this functional drink. This research is a pre-experimental research. The research design uses a one shot group design. The organoleptic analysis test used was the Friedman test. Product safety was carried out by microbiological contamination test using AMP and ALT methods. Organoletic test analysis showed that there was no difference in acceptance (p>0.005) of color, aroma, taste and texture at the concentration of gum addition (0.10%, 0.15% and 0.20%). Bacteriological test results AMP and ALT values do not exceed the maximum threshold value of microbial contamination according to SNI 3719:2014 for beverage products.          Keywords : Functional drink, arabic gum, pigeon pea, tempe  ABSTRAK Kacang gude dan tempe merupakan pangan lokal yang kaya dengan kandungan zat gizi. Minuman fungsional ini merupakan pengembangan dari formulasi minuman kacang gude yang telah dibuat sebelumnya. Minuman fungsioanal kacang gude dan tempe ini dengan penambahan gum arab sebagai bahan penstabil. Menganalisis pengaruh penambahan gum arab melalui uji organoleptik dan mengetahui keamanan pangan minuman fungsional ini. Penelitian ini merupakan penelitian pra ekperimental.   Desain penelitian menggunakan one shot group design. Uji analisis organoleptik yang digunakan adalah  uji Friedman. Keamanan produk dilakukan dengan uji cemaran mikrobiologi metode AMP dan ALT. Analisis uji organoletik adalah tidak ada perbedaan penerimaan (p>0,005) terhadap warna, aroma, rasa dan tektur pada konsentrasi penambahan gum (0,10%, 0,15% dan 0,20%).  Hasil uji bakteriologi nilai AMP dan ALT tidak melebihi nilai ambang batas maksimum cemaran mikroba menurut SNI 3719:2014 untuk produk minuman. Kata Kunci : Minuman fungsional, gum arab, kacang gude, tempe